Akuntabilitas Syariah sebagai Upaya Pencegahan Greenwashing dalam Pelaporan Keberlanjutan - Nur Laeli Musthofa; Mardiyansyah; Rustam Hanafi (Equivalent : Journal of Economic, Accounting and Management, 2026)
The rise of greenwashing in sustainability reporting has become a significant challenge as Environmental, Social, and Governance (ESG) disclosure obligations increase in Indonesia, without being accompanied by uniform reporting standards. This issue becomes more complex for entities claiming to operate under Shariah principles, since the risk of greenwashing may distort both spiritual substance and financial reputation. This article aims to examine and analyze the role of Shariah accountability, through the Shariah Enterprise Theory (SET) framework, as an effort to prevent greenwashing practices in corporate sustainability reporting. Using a conceptual literature review approach, this article synthesizes three bodies of literature: conventional theories of sustainability disclosure (legitimacy, stakeholder, and signaling theory), the concept and empirical evidence of greenwashing, and the framework of Shariah accountability along with its operational instruments. The findings indicate that the vertical dimension (accountability to Allah SWT) and horizontal dimension (accountability to people and nature) within SET can serve as an additional preventive layer against the structural weaknesses of conventional regulation, with the Shariah Supervisory Board (DPS) and maqasid-based indices serving as its operational instruments. Nevertheless, empirical evidence shows that the implementation of Shariah accountability still faces significant gaps, particularly in its horizontal dimension. This article contributes theoretically by positioning SET as an underexplored preventive framework against greenwashing, and practically by recommending an expansion of the Shariah Supervisory Board's function to also assess the substance of sustainability claims, not merely compliance with financial transactions. Abstrak  Isu greenwashing dalam pelaporan keberlanjutan menjadi tantangan signifikan seiring meningkatnya kewajiban pengungkapan Environmental, Social, and Governance (ESG) di Indonesia, tanpa disertai keseragaman standar pelaporan. Persoalan ini menjadi semakin kompleks pada entitas yang mengklaim beroperasi sesuai prinsip syariah, karena risiko greenwashing berpotensi mendistorsi substansi spiritual sekaligus reputasi keuangan. Artikel ini bertujuan mengkaji dan menganalisis peran akuntabilitas syariah, melalui kerangka Shariah Enterprise Theory (SET), sebagai upaya pencegahan praktik greenwashing dalam pelaporan keberlanjutan perusahaan. Menggunakan pendekatan studi literatur konseptual, artikel ini mensintesis tiga kelompok kajian: teori konvensional pengungkapan keberlanjutan (legitimasi, pemangku kepentingan, dan sinyal), konsep serta bukti empiris greenwashing, dan kerangka akuntabilitas syariah beserta instrumen operasionalnya. Hasil kajian menunjukkan bahwa dimensi vertikal (pertanggungjawaban kepada Allah SWT) dan horizontal (pertanggungjawaban kepada manusia dan alam) dalam SET berpotensi menjadi lapisan pencegahan tambahan atas kelemahan struktural regulasi konvensional, dengan Dewan Pengawas Syariah (DPS) dan indeks berbasis maqasid sebagai instrumen operasionalnya. Namun demikian, bukti empiris menunjukkan bahwa implementasi akuntabilitas syariah masih menyisakan kesenjangan, terutama pada dimensi horizontal. Artikel ini berkontribusi secara teoretis dengan memposisikan SET sebagai kerangka preventif greenwashing yang belum banyak dieksplorasi, sekaligus secara praktis dengan merekomendasikan perluasan fungsi DPS agar turut menilai substansi klaim keberlanjutan, tidak hanya kepatuhan transaksi keuangan